Simulation of torsion of a cylindrical gel - Wong, Melissa Shi Yuen. (2013)
Hydrogels are widely used for many biomedical as well as commercial purposes such as scaffolds for tissue engineering, contact lenses and diapers. However, there is still much unexplored potential of this substance which could very well contribute to more medical advances and breakthroughs. It is therefore important to understand the mechanical properties of hydrogels for this purpose. This project aims to understand the effect of torsion on hydrogels in a cylindrical form.